PENGARUH DZIKIR PRE OPERASI DENGAN GENERAL ANESTESI TERHADAP KECEMASAN PASIEN - Fadil M.Rizqi; Wahyu Riyaningrum; Budi Joko Santoso; Rully Annisa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Preoperative anxiety is a prevalent psychological reaction observed in patients before to surgical interventions, potentially impai ring mental preparedness, anesthetic procedures, and postoperative recovery. Dhikr therapy, which involves remembering God, is one of the non-pharmacological methods that have gained popularity as supplemental anxiety management techniques. Examin ing how dhikr treatment affected preoperative anxiety levels in patients receiving general anesthesia at RST Wijaya Kusuma Purwokerto was the goal of this study. One-group pretest–posttest methodology was used in a pre-experimental study design. Purposive sampling was used to choose the 33 preoperative patients undergoing general anesthesia who made up the study sample. Prior to and following the application of dhikr treatment, anxiety levels were assessed. The Shapiro-Wilk test was used to determine normality in the data, and the wilcoxon was used to compare anxiety scores. Anxiety levels significantly decreased after the intervention, according to the statistical analysis, with a signi ficance value of 0.001 (p < 0.05). These results suggest that dhikr ther apy reduces preoperative anxiety in a statistically significant way. In conclusion, dhikr therapy can be regarded as a secure and efficaci ous non-pharmacological technique for alleviating anxiety in preoperative patients general anesthesia at RST Wijaya Kusuma Purwokerto.